Cardiac damage after lesions of the nucleus tractus solitarii - Nayate, Ameya (American Physiological Society, 2009)
Humans with central lesions that augment sympathetic nerve activity are predisposed to cardiac arrhythmias, myocardial lesions, and sudden death. Previously, we showed that selectively killing neurons with neurokinin-1 receptors in the nucleus tractus solitarii (NTS) of rats attenuated the baroreflex and, in some animals, led to sudden unexplained death within ∼2 wk. Interruption of arterial baroreflexes is known to increase sympathetic activity. Here we tested the hypothesis that lesions in the NTS lead to fatal cardiac arrhythmias and myocardial lesions. We studied electrocardiograms, echocardiograms, blood pressure, and heart rate in 14 adult male rats after bilateral microinjection into the NTS of stabilized substance P conjugated to the toxin saporin and compared the variables in five sham control rats and in five animals with toxin injected outside the NTS. Only injection of toxin into the NTS led to increased lability of arterial blood pressure, a sign of baroreflex interruption. Two animals treated with toxin died suddenly. All animals engaged in normal activity until, in two, rapid development of asystole and death over 6–8 min. Cardiac function when examined by echocardiography was normal, but pathologic examination of the heart revealed diffuse microscopic areas of acute coagulation necrosis in the myocardium in five animals, focal subacute necrosis in two animals, and both changes in one animal. This study supports the hypothesis that NTS lesions interrupting the baroreflex may induce cardiac arrhythmias and myocardial changes similar to those seen in humans with central lesions and may lead to sudden cardiac death.